2019
DOI: 10.2174/1381612825666190329145428
|View full text |Cite
|
Sign up to set email alerts
|

Valproic Acid and the Liver Injury in Patients with Epilepsy: An Update

Abstract: Background: Valproic acid (VPA) as a widely used primary medication in the treatment of epilepsy is associated with reversible or irreversible hepatotoxicity. Long-term VPA therapy is also related to increased risk for the development of non-alcoholic fatty liver disease (NAFLD). In this review, metabolic elimination pathways of VPA in the liver and underlying mechanisms of VPA-induced hepatotoxicity are discussed. Methods: We searched in PubMed for manuscripts published in English, combining terms such as “… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(41 citation statements)
references
References 83 publications
0
40
0
1
Order By: Relevance
“…The hepatotoxicity of valproic acid in patients with epilepsy has been reviewed. 23 These authors summarized the available mechanistic literature regarding formation of valproic acid reactive metabolites, excess oxidative stress, altered fatty acid metabolism, and genetic variants of some enzymes such as glutathione transferases, uridine diphosphate (UDP)-glucuronosyltransferases, superoxide dismutase, and mitochondrial polymerase gamma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The hepatotoxicity of valproic acid in patients with epilepsy has been reviewed. 23 These authors summarized the available mechanistic literature regarding formation of valproic acid reactive metabolites, excess oxidative stress, altered fatty acid metabolism, and genetic variants of some enzymes such as glutathione transferases, uridine diphosphate (UDP)-glucuronosyltransferases, superoxide dismutase, and mitochondrial polymerase gamma.…”
Section: Discussionmentioning
confidence: 99%
“…Both CBD and valproic acid are known to undergo metabolism, and a metabolite of valproic acid (2-enevalproic acid) has been shown to be hepatotoxic. 23,24 Because here are some structural similarities between the metabolites of CBD and valproic acid, CBD may potentiate the hepatotoxicity of valproic acid via this mechanism. 24 Several animal studies have specifically addressed the potential hepatotoxic effects of CBD-containing products.…”
Section: Discussionmentioning
confidence: 99%
“…Through the action of liver 25hydroxylase, human exogenous and endogenous Vitmin D2 and D3 are converted into 25-OH-VitD, which requires the action of 1-α hydroxylase in the proximal tubule of the kidney to form active 1-25-OH-VitD [27]. Previous studies suggest that both valproic acid and its intermediate metabolite 4-ene-VPA can be hepatotoxic, especially to mitochondrial function, which can affect the hydroxylation function of liver and kidney through inhibiting the activity of P450 isozyme CYP2C191 and uridine diphosphate transferase, thus further affect the synthesis of 1, 25-OH-VitD [28,29].…”
Section: --mentioning
confidence: 99%
“…Long-term VPA therapy has also been reported to be associated with an increased risk for the development of nonalcoholic fatty liver disease. 15 There have been many studies to evaluate the effects of antiepileptic drugs (AEDs) on liver function in children with epilepsy; however, these studies revealed divergent results. Furthermore, there is limited information on the effect of VPA on the liver enzymes in pediatric patients with epilepsy in Nigeria.…”
Section: Introductionmentioning
confidence: 99%